Incidence of SARS-CoV-2 reinfection in a paediatric cohort in Kuwait - Mohammad Alghounaim; Saadoun Bin-Hasan; Fatemah Alhaddad; Ali Abdulkareem; Danah Alsharrah; Abdullah Alkandari; Mona Al-Ahmad; Hashem Al Hashemi (BMJ Open)
Objective Subsequent protection from SARS-CoV-2 infection in paediatrics is not well reported in the literature. We aimed to describe the clinical characteristics and dynamics of SARS-CoV-2 PCR repositivity in children.Design This is a population-level retrospective cohort study.Setting Patients were identified through multiple national-level electronic COVID-19 databases that cover all primary, secondary and tertiary centres in Kuwait.Participants The study included children 12 years and younger between 28 February 2020 and 6 March 2021. SARS-CoV-2 reinfection was defined as having two or more positive SARS-CoV-2 PCR tests done on a respiratory sample, at least 45 days apart. Clinical data were obtained from the Pediatric COVID-19 Registry in Kuwait.Primary and secondary outcome measures The primary measure is to estimate SARS-CoV-2 PCR repositivity rate. The secondary objective was to establish average duration between first and subsequent SARS-CoV-2 infection. Descriptive statistics were used to present clinical data for each infection episode. Also, incidence-sensitivity analysis was performed to evaluate 60-day and 90-day PCR repositivity intervals.Results Thirty paediatric patients with COVID-19 had SARS-CoV-2 reinfection at an incidence of 1.02 (95% CI 0.71 to 1.45) infection per 100 000 person-days and a median time to reinfection of 83 (IQR 62–128.75) days. The incidence of reinfection decreased to 0.78 (95% CI 0.52 to 1.17) and 0.47 (95% CI 0.28 to 0.79) per person-day when the minimum interval between PCR repositivity was increased to 60 and 90 days, respectively. The mean age of reinfected subjects was 8.5 (IQR 3.7–10.3) years and the majority (70%) were girls. Most children (55.2%) had asymptomatic reinfection. Fever was the most common presentation in symptomatic patients. One immunocompromised experienced two reinfection episodes.Conclusion SARS-CoV-2 reinfection is uncommon in children. Previous confirmed COVID-19 in children seems to result in a milder reinfection.